Power Relations and Sexual Violence on the Campus - Irianto, Sulistyowati (Jurnal Perempuan, 2021)
Sexual violence on campus is a crime against humanity that is difficult to uncover because of professors’ power relations and domination over students. Power relations also manifest at the structural level so that sexual violence is often dismissed and silenced by the administrators. The campus environment’s hierarchy of status and positions makes sexual crime cases go on for years without any accountability. On the other hand, there are efforts such as the collective action of lecturers across faculties to protect victims from the perpetrators and bring the perpetrators to justice. This study describes the author’s experience in dealing with sexual violence on campus and using a reflexive approach in addressing sexual violence in Indonesia.